Training needs in schools integrating students with disabilities in Tartous Governorate (A Field Study on Inclusive Classroom Teachers and Resource Room Teachers) (Journal of Hama University, 2026)
The current research aimed to identify the training needs of inclusive classroom teachers in inclusive schools in Tartous Governorate and to explore differences in these needs based on the school’s location and whether teachers had attended training courses on inclusive education.The researcher designed a Training Needs Questionnaire and applied it to a stratified random sample of 212 teachers, employing the descriptive method. The findings revealed that teachers had a moderate level of training needs, both in the overall score of the questionnaire and its individual domains.Training needs related to skills ranked first, followed by those related to theoretical knowledge. Within the skills domain, the needs were ranked from most to least important as follows: (1) skills related to managing inclusive classrooms, (2) teaching skills, (3) assessment skills, and (4) skills related to teaching aids.The study found no differences in training needs based on the location of schools (urban vs. rural). However, teachers who had not attended training courses on inclusive education exhibited higher training needs compared to those who had participated in such courses.
Keywords: Training Needs, Inclusive Education, Inclusive schools, Inclusive School Teachers, Resource Room Teachers